Managing groundwater supplies subject to drought: An English perspective on current status and future priorities - Ascott, Matthew J.; Bloomfield, John P.; Karapanos, I.; Jackson, C. R.; Ward, R. S.; McBride, A. B.; Dobson, B.; Kieboom, N.; Holman, Ian P.; Van Loon, A. F.; Crane, E. J.; Brauns, B.; et al. (Springer, 2020)
Effective management of groundwater resources during drought is essential. How is groundwater currently managed during droughts, and in the face of environmental change, what should be the future priorities? Four themes are explored, from the perspective of groundwater management in England (UK): (1) integration of drought definitions; (2) enhanced fundamental monitoring; (3) integrated modelling of groundwater in the water cycle; and (4) better information sharing. Whilst these themes are considered in the context of England, globally, they are relevant wherever groundwater is affected by drought.
Keywords: UK; Drought; Water supply; Groundwater management